Komunikasi Terapeutik Pada Pasien Dengan Gangguan Mental: Studi Kualitatif Pada Psikoterapis - Almadina Rakhmaniar (Institut Nalanda, 2023)
Therapeutic communication plays an important role in the interaction between psychotherapists and patients with mental disorders. An in-depth understanding of effective communication strategies can improve the quality of therapy and treatment outcomes. This study aimed to explore the communication techniques and approaches used by psychotherapists in treating patients with mental disorders.This study used a qualitative approach with a case study method. Data were collected through in-depth interviews with 10 psychotherapists practicing in Bandung City. Data were analyzed using thematic analysis techniques to identify key themes related to effective therapeutic communication strategies. The results revealed several key themes in therapeutic communication, including: (1) The use of empathy and emotional validation to build a relationship of trust; (2) The application of nonverbal communication techniques, such as eye contact and supportive body language; (3) The adaptation of language and terminology according to the patient's condition and needs; (4) A collaborative approach in setting therapy goals and action plans; and (5) The importance of openness and transparency in communication to increase patient involvement in the therapy process. The study concluded that effective therapeutic communication requires a combination of empathy, appropriate nonverbal communication techniques, language adaptation, collaborative approach and openness. Psychotherapists who successfully implement these strategies can create a supportive therapeutic environment and improve the effectiveness of treatment for patients with mental disorders. These findings provide important insights for psychotherapy practice and professional training in the mental health field.